The Impact of Green Finance Policy on Corporate ESG Performance：Evidence from China’s Listed Companies - Gao, Yuyang (2022)
After decades of exploration and development, China's green financial market has initially established a green financial system framework and formed the concept of green development. China has now entered an accelerated period for the formation of a green financial policy system. The Chinese government integrates the sustainable development into the development strategy of enterprises through policy guidance. However, the current empirical research is relatively lacking, mainly focusing on qualitative analysis. At the same time, as China has set out the aims of "3060" and "carbon peaking and carbon neutrality" in recent years, ESG has gradually become an important factor that cannot be ignored in the development of enterprises. The development goals of enterprises have also shifted from pursuing a single economic benefit to the mutual development of economic benefits and social benefits. With the gradual improvement of the current systematic ESG rating system, a large amount of data shows no contradiction between obtaining economic benefits and practising social responsibility. In light of this, the paper aims to investigate whether green finance policy impacts Chinese listed companies' ESG performance. This paper selects Chinese listed companies registered in the pilot zones announced in 2017 as research object. Eighty-one listed companies from 2014 to 2020 were taken as the samples of this study. A DID model was built to analyze the impact of China’s green finance policies. According to the empirical evidence of this study, after the policy is implemented in the pilot area, the ESG performance of listed companies has positive correlation with the policy implementation. It shows that green finance policy can effectively promote enterprises to improve ESG performance. However, when the heterogeneity analysis is carried out, the implementation effect of green finance policy shows different results for enterprises of different scales. Implementing green finance policies can significantly improve the ESG scores of large-scale enterprises, while it negatively affects small and medium-sized enterprises. Based on theoretical and empirical research results, this paper gives suggestions and countermeasures for policy optimization in the pilot zones. The research content and conclusions of this paper have a certain role in evaluating the policy effects and have policy guidance implications. At the same time, it also have a certain guiding role in discussing the ESG performance of enterprises under the conditions of green financial policies.